N-Doping of photoactive layer in binary organic solar cells realizes over 18.3% efficiency. (1st June 2022) - Li, Danqin; Geng, Fushan; Hao, Tianyu; Chen, Zeng; Wu, Hongbo; Ma, Zaifei; Xue, Qifan; Lin, Lina; Huang, Rong; Leng, Shifeng; Hu, Bingwen; Liu, Xianjie; et al.
Abstract: Electronic doping of conjugated semiconductor plays a critical role in the fabrication of high efficiency organic optoelectronic devices. Here, we report an organic solar cell (OSC) by doping n -type DMBI-BDZC into one host binary bulk heterojunction (BHJ) photoactive layer comprised of a polymer donor PM6 and a nonfullerene acceptor Y6. The resulting champion device yields a significantly improved power conversion efficiency from 17.17% to 18.33% with an impressive fill factor of 80.20%. It is found that the electrically doped photoactive layer exhibits enhanced and balanced charge carrier mobilities, more effective exciton dissociation, longer carrier lifetime, and suppressed charge recombination with smaller energy loss. The dopant molecule DMBI-BDZC also act as a surface morphology modifier of the photoactive layer with enhanced charge transport. This work demonstrates that manipulation of charge transport via adding a low concentration dopant into photoactive layer is a promising approach for further improvement of BHJ OSC performance. Graphical Abstract: ga1 By n-doping DMBI-BDZC into PM6:Y6 blend, the solar cell efficiency was enhanced from 17.17% to 18.33% with a fill factor of 80.20%. Highlights: The doping enhanced solar cell efficiency from 17.17% to 18.33% with an impressive fill factor of 80.20%. The doping improves exciton dissociation and suppresses charge recombination with smaller energy loss. The dopant also acts as a morphology modifier to improve charge transport.